Impact of constituent development fund allocations on the performance of South Sulawesi provincial library and archives office - Hamudy, Moh Ilham A; Annisa, Mutiara Lulu; Rifki, M S (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
The decision of the South Sulawesi Provincial Government to suspend the Regional House of Representatives grant, known as the Constituent Development Fund, adversely affected the programs and activities of the South Sulawesi Provincial Library and Archives Office. Budget allocation is a critical support of the achievement of the Community Literacy Development Index and Reading Interest Index. The purpose of this study is to analyze the impact of the management of the Constituent Development Fund on the Library and Archives Office of South Sulawesi Province and provide solutions to address the problems related to the fund allocation. A mixture of descriptive and literature study methods was used, while a qualitative approach was used for data analysis. Analysis of the 2023 data shows that the South Sulawesi Provincial Library and Archives Office depends heavily on the Constituent Development Fund to finance its programs and activities. The library office had difficulty in reaching the targets of the Community Literacy Development Index and Reading Interest Level when the Constituent Development Fund was suspended and reallocated to pay the provincial government's debt. The budget uptake was inhibited, impacting on the execution of strategic programs that correlate to an increase in the human development index.